O luxo falsificado e suas formas de consumo - Strehlau, Suzane (2004)
The concept of a luxury is dynamic and historical, belonging to a society in a particular moment and venue. As its consumption is widespread, it ceases to represent a social distinction. The luxury is not in the object itself, but in the judgment of a person on its value. The knowledge on luxury brands is sophisticated and requires specific qualifications. Not all prestigious products are necessarily a luxury and within the luxury category there is a scale of prestige. Taste, although it has a portion of individual origin, is shaped by the environment, and this will influence the attitudes and the behavior in consumption and socialization. The Habitus theory by Bourdieu offers an explanation based on the space of social positions organized around three dimensions: the total volume of social, cultural and economical capital, its composition and path taken over time. The cultural form of the incorporated capital, the habitus, implies in the assimilation of cultural conditions. The knowledge about false brands and their corresponding genuine items allow the owner to show all of ones habitus, that incorporated knowledge that only time and dedication can generate. The various origins and types of forgeries allow for showing a specific knowledge. The manner of relating oneself with the forged product, the manner of using them, how to cope with the subject in front of others in a social interaction generate an exhibition of habitus. The interviewed consumer of a habitus resulting from the stability in the popular stratum demonstrates little brand knowledge, being restricted to a name and a label. The ancestral nature in the elite stratum assures a tranquility in the consumption of forgeries, since, as tastemakers, they may express their distance from the need and their possibility of imposing the rules for distinction. For the group interviewed showing a recent social mobility, the forged brand may be used as leverage to increase social capital. When the social space occupied is still unstable, there continue to be reflections of social mobility, the brand is used as a crutch for generating connections, demonstrating a social position to those who are not a part of ones most intimate group of relations. The forged product may be a demonstration of distinction, if used suitably, with elements allied with the consumption by the dominant class.